The view from above: Unmanned aerial systems and remote scouting for insects. Issue 3 (24th August 2016) - MacRae, Ian; Koch, Robert; Alves, Tavvs; Marsten, Zach; Baker, Tim; Gebre-Egziabher, Demoz; Taylor, Brian; Olson, Curtis; Regan, Chirs; Hurley, Terrance
Abstract : Fitting insect management into precision agriculture is a challenge. Recent advances in remote sensors, especially near‐infrared (NIR) cameras, are providing more affordable ways to assess plant health. The concurrent developments in unmanned aerial systems (UAS or drones) have also provided an ideal platform for deploying these sensors. Earn 0.5 CEUs in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/782 .